The advanced producer services complex as an obligatory passage point: evidence from rent extraction by investment banks - Pazitka, V; Bassens, D; van Meeteren, M; Wójcik, D (SAGE Publications, 2021)
Advanced producer services have long been theorized as pivotal in organizing the global economy. Finance takes centre stage in the advanced producer services complex as orchestrator of global flows, particularly in underwriting investment and evaluating corporate performance. The ascent of financialized globalization raises the suspicion that key advanced producer services act as rent-extracting ‘obligatory passage points’ in the orchestration of global financial flows. Competition within the financial sector is contentious given the sustained profits by globally connected banks operating in concentrated markets. Investment banks and other advanced producer services play key roles in underwriting of securities, raising questions whether underwriting is a competitive process. This paper interrogates the microeconomic foundations for the role of investment banks in investment chains to shed light on their rent extraction practices. Using a sample of 2940 initial public offerings for the USA, Canada, and Europe in the 1998–2017 period, we examine the structure of fees charged by investment banks for underwriting of equity securities. Our results are consistent with the proposition that investment banks with more market power and stronger network ties with institutional investors utilize their dominant position in the marketplace to extract rents from both issuers and institutional investors. Taken together, at times of spatial and sectoral consolidation, these results show compelling evidence for the status of investment banks and by extension the wider advanced producer services complex as obligatory passage points under financialized globalization.